UMP owns 180-acre of land - Asdarina, Yahya (Penerbit UMP, 2012)
The Deputy Vice Chancellor Prof Dato' Dr. Rosli bin Mohd Yunus mooted the idea for land application as he found out that most of the studies conducted by the university's researchers were agro-based. Efforts taken to apply for the land began in 2009.